Accuracy of stridor‐based diagnosis of post‐intubation subglottic stenosis in pediatric patients - Cláudia Schweiger; Larissa Valency Eneas; Denise Manica; Cátia de Souza Saleh Netto; Paulo Roberto Antonacci Carvalho; Jefferson Pedro Piva; Gabriel Kuhl; Paulo José Cauduro Marostica (Brazilian Society of Pediatrics, 2020)
Objective: To assess the accuracy of stridor in comparison to endoscopic examination for diagnosis of pediatric post‐intubation subglottic stenosis. Method: Children who required endotracheal intubation for >24 h were included in this prospective cohort study. Children were monitored daily and underwent flexible fiberoptic laryngoscopy after extubation. Those with moderate‐to‐severe abnormalities underwent another examination 7-10 days later. If lesions persisted or symptoms developed, laryngoscopy under general anesthesia was performed. Patients were assessed daily for stridor after extubation. Results: A total of 187 children were included. The incidence of post‐extubation stridor was 44.38%. Stridor had a sensitivity of 77.78% (95% confidence interval [95% CI]: 51.9-92.6) and specificity of 59.18% (95% CI: 51.3-66.6) in detecting subglottic stenosis. The positive predictive value was 16.87% (95% CI: 9.8-27.1), and the negative predictive value was 96.15% (95% CI: 89.9-98.8). Stridor persisting longer than 72 h or starting more than 72 h post‐extubation had a sensitivity of 66.67% (95% CI: 41.2-85.6), specificity of 89.1% (95% CI: 83.1-93.2), positive predictive value of 40.0% (95% CI: 23.2-59.3), and negative predictive value of 96.07% (95% CI: 91.3-98.4). The area under the receiver operating characteristic (ROC) curve was 0.78 (95% CI: 0.65-0.91). Conclusions: Absence of stridor was appropriate to rule out post‐intubation subglottic stenosis. The specificity of this criterion improved when stridor persisted longer than 72 h or started more than 72 h post‐extubation. Thus, endoscopy under general anesthesia can be used to confirm subglottic stenosis only in patients who develop or persist with stridor for more than 72 h following extubation. Resumo: Objetivo: Analisar a precisão do estridor em comparação com o exame endoscópico no diagnóstico de estenose subglótica pós‐intubação em crianças. Método: Foram incluídas neste estudo de coorte prospectivo crianças que necessitaram de intubação endotraqueal por mais de 24 horas. Elas foram monitoradas diariamente e submetidas à nasofibrolaringoscopia flexível após a extubação. As crianças com anomalias moderadas foram submetidas a outro exame sete a 10 dias depois. Caso as lesões persistissem ou os sintomas evoluíssem, a laringoscopia era realizada com anestesia geral. Os pacientes foram avaliados diariamente quanto ao estridor após a extubação. Resultados: Participaram 187 crianças. A incidência de estridor após a intubação foi de 44,38%. O estridor apresentou uma sensibilidade de 77,78% (intervalo de confiança de 95% [IC]: 51,9‐92,6) e especificidade de 59,18% (IC: 51,3‐66,6) na detecção de SGS. O valor preditivo positivo foi de 16,87% (IC: 9,8‐27,1) e o valor preditivo negativo (VPN) foi de 96,15% (IC: 89,9‐98,8). O estridor que persistiu por mais de 72 horas ou que começou 72 horas após a extubação teve uma sensibilidade de 66,67% (IC: 41,2‐85,6), especificidade de 89,1% (IC: 83,1‐93,2), valor preditivo positivo de 40,0% (IC: 23,2‐59,3) e valor preditivo negativo de 96,07% (IC: 91,3‐98,4). A área sob a curva de característica de operação do receptor (ROC) foi de 0,78 (IC: 0,65‐0,91). Conclusões: A ausência de estridor foi adequada para descartar a estenose subglótica pós‐intubação. A especificidade desse critério melhorou quando o estridor perdurou por mais de 72 horas ou começou mais de 72 horas após a extubação. Assim, a endoscopia com anestesia geral pode ser utilizada para confirmar a estenose subglótica somente em pacientes que desenvolveram ou continuaram com estridor por mais de 72 horas após a extubação. Keywords: Stridor, Laryngoscopy, Acquired subglottic stenosis, Intubation, Accuracy, Palavras‐chave: Estridor, Laringoscopia, Estenose subglótica adquirida, Intubação, Precisão